In Vitro Antiprotozoal Activity of Schinus molle Extract, Partitions, and Fractions against Trypanosoma cruzi - Rodríguez Garza, Nancy Edith; Quintanilla Licea, Ramiro; Gomez Flores, Ricardo; Galaviz Silva, Lucio; Molina Garza, Zinnia Judith (Multidisciplinary Digital Publishing Institute, 2024)
Chagas disease, caused by the protozoan Trypanosoma cruzi, represents an important and worldwide public health issue, particularly in Latin America. Limitations of conventional treatment with benznidazole and nifurtimox underscore the urgent need for new therapeutic strategies for this disease. Schinus molle, a tree used in traditional medicine for various ailments, has demonstrated promising antiparasitic activity. The in vitro anti-T. cruzi activity of Schinus molle crude methanol extract, partitions, and fractions, as well as their cytotoxicity in Vero cells and Artemia salina, and hemolytic activity in human erythrocytes were assessed. Most of the extracts possessed anti-T. cruzi effects, with Sm-CF3 being the fraction with the highest activity (IC50 = 19 μg/mL; SI = 6.8). Gas chromatography–mass spectrometry analysis identified 20 compounds, with fatty acyls comprising the predominant chemical class (55%). We also identified the antiparasitic compounds cis-5,8,11,14,17- eicosapentaenoic acid and trans-Z-α-bisabolene epoxide, suggesting their potential contribution to the observed anti-T. cruzi activity. In conclusion, our findings support the therapeutic potential of S. molle as a source of novel antiparasitic agents against T. cruzi.